Transcendence a úzkost - Benyovszky, Ladislav (Lidé města, 2002)
The reflection is concerned with the concept of man arising at the time when philosophy started to doubt about the validity of the "subject-object" concept of the world. In contradiction with the previous concept of subjectivity, philosophy sees the man in relation to himself, as the "self-relationship" (Selbstbezug). As in this case this cannot be "an object relationship," it is a concept stressing the motive of "mood," "atmosphere" and usually anguish. The reflection explains the problem by citing the historically first form, in Kierkegaarďs concept of the "relationship to oneself."